Bistatic microwave imaging with different transmission positions using multiband sensors for breast tumor detection - Misman, Dalila; Rahman, Nurul Huda Abd; Abd. Aziz, Mohamad Zoinol Abidin (2024)
Microwave imaging is a promising technique for detecting breast tumors, offering an alternative to conventional medical imaging modalities. This study investigates the use of a bistatic microwave imaging system with multiband sensors and different transmission positions to improve the detection of breast cancer. A homogeneous breast phantom model was developed to simulate the dielectric properties of biological breast tissues, including the skin, fat, and tumor. The study evaluated the performance of the system under two antenna transmission conditions - horizontal (azimuth angle) and vertical (polar angle) positions. Simulation results show that the transmission coefficient (S21) can effectively detect tumors as small as 4 mm in size using both horizontal and vertical transmission positions.